Investigating the role of eIF4A2 in the spatial regulation of metabolic adaptation to hypoxia in colorectal cancer - Thornton, Luke (2023)
Colorectal cancer is the third most common cancer worldwide and ranks second for cancer-related mortality. Hypoxia (< 1% pO2) is found in up to 50% of colorectal tumours and is associated with poor patient prognosis, increased metastatic potential and resistance to therapy. Hypoxia stabilises the hypoxia-inducible factors, HIF-1ɑ and HIF-2ɑ, to alter the transcriptome to drive molecular adaptation to hypoxic stress. Hypoxia also leads to changes in the translation machinery to alter protein synthesis. The changes introduced by these mechanisms contribute to the major hallmarks of cancer including metabolic reprogramming. However, how the oxygen gradient in tumours contributes to spatially defined metabolic adaptations and how this leads to therapeutic failure is unknown. Preliminary data hypothesised that the translation initiation factor eIF4A2 is a modulator of hypoxic adaptation and regulates colorectal cancer cell survival through the regulation of metabolic mRNA translation. Here, the eIF4A2 interaction landscape was investigated and revealed hypoxic interactions with other regulators of mRNA translation including eIF4G3, eIF4E1 and CNOT7. eIF4A2 knockout was shown to reduce spheroid growth and led to an increase in HIF-2ɑ expression. Furthermore, the expression of several predicted eIF4A2 target genes involved in amino acid biosynthesis and endocytosis were investigated. eIF4A2 knockout led to a reduction in the expression of the endocytosis regulator EHD1 and EHD1 knockdown reduced cancer cell survival. This work suggests eIF4A2 regulates the hypoxic translation of specific mRNAs, such as EHD1, through altered protein:protein interactions to regulate colorectal cancer cell survival. Moreover, a novel secondary ion mass spectrometry imaging technique for spatially resolving metabolite changes across the oxygen gradient within 3-D spheroid models and colorectal cancer xenografts is revealed. We pioneer high-pressure frozen orbiSIMS to simultaneously measure metabolites in situ across differentially oxygenated regions of tumours and colorectal cancer spheroid models. Correlation with RNA-sequencing helps predict the transcriptional changes behind this spatial metabolic adaptation and could be used to identify novel therapeutic targets important for tackling therapeutic resistance driven by hypoxia-induced metabolic reprogramming.